UTD-PO Solutions for the Analysis of Multiple Diffraction by Trees and Buildings When Assuming Spherical-Wave Incidence - Rodríguez, José-Víctor; Martínez-Inglés, María-Teresa; Molina Garcia-Pardo, Jose-Maria; Juan-Llácer, Leandro; Rodríguez-Rodríguez, Ignacio (My University, 2023)
This paper presents two uniform theories of diffraction–physical optics (UTD-PO) formulations to undertake analysis of radiowave multiple diffraction resulting from the presence of both buildings and trees in vegetated urban areas, with the assumption of spherical-wave incidence. The solutions presented consider buildings modeled as knife-edges and rectangular sections (the latter being more complex and realistic) and the effect of the tree canopy (the assumption is that this exceeds the height of the average rooftop) is taken into account by adding proper attenuation factors/phasors to building diffraction phenomena. The validation of these formulations has been undertaken by comparing with other methods and measurements performed at 39 GHz on a scaledmodel of the environment under analysis, consisting of an array of bricks and bonsai trees. The chief advantage of the solutions put forward is that because of recursion, the calculations only include single diffractions. This avoids any requirement for higher-order diffraction terms in the diffraction coefficients, which means less computer time/power is demanded. The results of this work may be useful when planning future mobile communication systems, including 6G networks and beyond.
Keywords: Sistemas de comunicaciones móviles; Multiple diffraction; Uniform theory of diffraction; Vegetation; Mobile communication